2015
DOI: 10.1515/eces-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flowback Water on Activated Sludge Biocenosis During Municipal Wastewater Treatment

Abstract: Abstract:The aim of this study was to determine the effect of flowback water on an activated sludge biocenosis during municipal wastewater treatment in the sequencing batch reactors (SBRs). Two series were performed. In series 1, only municipal wastewater was treated, whereas in series 2, municipal wastewater with pre-treated flowback water was used. Flowback water constituted 3-5% of the influent and was introduced to the SBRs twice per week. Introducing flowback water did not decrease the quality of effluent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Total bacterial DNA from resistant strains obtained from CW columns was isolated with a mechanical method as previously described (Ziembińska-Buczyńska et al, 2015). The 180 bp amplicons of partial 16S rRNA coding genes were generated with the PCR method according to the previous procedure (Muyzer et al, 1993).…”
Section: The Presence Of Smx-resistant Bacterial Genotypes In Cw Commmentioning
confidence: 99%
“…Total bacterial DNA from resistant strains obtained from CW columns was isolated with a mechanical method as previously described (Ziembińska-Buczyńska et al, 2015). The 180 bp amplicons of partial 16S rRNA coding genes were generated with the PCR method according to the previous procedure (Muyzer et al, 1993).…”
Section: The Presence Of Smx-resistant Bacterial Genotypes In Cw Commmentioning
confidence: 99%
“…Studies carried out in biological water treatment plants demonstrated that microfauna involved in biological treatment are sensitive to the changes in environmental conditions of the aeration tank (Arregui et al, 2013;Foissner, 2016;Pedrazzani et al, 2016;Ziembi´nska-Buczy´nska et al, 2015). Functional groups, species, or lower rank taxons can be used as biological indicators and assist in the evaluation of conditions inside the aeration tank or the performance of the system itself (dos Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%